α4βδ GABAA receptors and tonic inhibitory current during adolescence: effects on mood and synaptic plasticity - Smith, Sheryl S. (Frontiers in Neural Circuits, 2013)
The onset of puberty is associated with alterations in mood as well as changes in cognitive function, which can be more pronounced in females. Puberty onset in female mice is associated with increased expression of α4βδ γ-amino-butyric acid-A (GABAA) receptors (GABARs) in CA1 hippocampus. These receptors, which normally have low expression in this central nervous system (CNS) site, emerge along the apical dendrites as well as on the dendritic spines of pyramidal neurons, adjacent to excitatory synapses where they underlie a tonic inhibition that shunts excitatory current and impairs activation of N-methyl-D-aspartate (NMDA) receptors, the trigger for synaptic plasticity. As would be expected, α4βδ expression at puberty also prevents long-term potentiation (LTP), an in vitro model of learning which is a function of network activity, induced by theta burst stimulation of the Schaffer collaterals to the CA1 hippocampus. The expression of these receptors also impairs spatial learning in a hippocampal-dependent task. These impairments are not seen in δ knock-out (-/-) mice, implicating α4βδ GABARs. α4βδ GABARs are also a sensitive target for steroids such as THP ([allo]pregnanolone or 3α-OH-5α[β]-pregnan-20-one), which are dependent upon the polarity of GABAergic current. It is well-known that THP can increase depolarizing current gated by α4βδ GABARs, but more recent data suggest that THP can reduce hyperpolarizing current by accelerating receptor desensitization. At puberty, THP reduces the hyperpolarizing GABAergic current, which removes the shunting inhibition that impairs synaptic plasticity and learning at this time. However, THP, a stress steroid, also increases anxiety, via its action at α4βδ GABARs because it is not seen in δ -/- mice. These findings will be discussed as well as their relevance to changes in mood and cognition at puberty, which can be a critical period for certain types of learning and when anxiety disorders and mood swings can emerge.